PO209 Proximal lower limb myopathy associated with ro52 antibody. (1st December 2017) - Theochari, Evangelia; Bridges, Leslie; Warner, Graham
Abstract : Introduction: Idiopathic inflammatory myopathies (IIM) represent a heterogeneous group of systemic disorders. We present a case of proximal lower limb weakness due to myopathy associated with Ro52 antibody. Case: A 76-year-old female presented initially with a 1½ year history of leg weakness and fatigue. One year later she remains mobile and paces herself through everyday life activities, but reports a 'lead-like' sensation of her legs when fatigued by walking. The only finding on bedside neurology examination is mild proximal hip flexion weakness but retained the ability to rise unaided from supine. Extensive initial investigation detected Ro52 antibody positivity with normal ESR and muscle enzymes, including CK. Neurophysiology was normal. MRI of the neuroaxis and thighs were unremarkable. Repeat EMG one year later revealed a mild myopathic pattern despite repeat normal CK. Muscle biopsy was essentially normal, apart from a few moth-eaten fibres. Ro52 associated myopathy was diagnosed and immunomodulatory treatment initiated. Discussion: This is a rare case of Ro52 associated myopathy with normal muscle enzymes throughout the mild illness, initially normal EMG examination and a non-diagnostic muscle biopsy. Diagnosis was supported by interval neurophysiology and the clinical response to treatment.